Factors affecting inappropriate prescribing of antibiotics and the emergence of antibiotic resistance in patients in primary health care - Opancina, Valentina D; Raspopovic, Katarina; Jankovic, Slobodan (Medicinski časopis, 2017)
Introduction. Increasing resistance to antibiotics is of great importance for health professionals around the world. The correlation between the use of antibiotics and rates of resistance has long been established. Physicians who work in primary health care make up a large part of health care personnel responsible for the use of these drugs. This study reveals factors that influence unduly prescribing antibiotics and the emergence of resistance to antibiotics in primary health care. Methodology. This study has been conducted at the Health center Danilovgrad, Montenegro from November 1st 2015 to June 1st 2016. We used a qualitative method - focus group, where one group consists of 8 members (six doctors for adults, 1 pediatrician am 1 pharmacist) and moderator. Based on previous systematic reviews, we made the agenda, which was followed during the group meetings to facilitate the identification of factors. During discussions within the meetings group audio recordings were made, and then their transcripts were individually analyzed by the researchers. Results. Our study showed that factors affecting the prescription of medicines in primary health care are: personal interest of referring physician; fear of referring physician; external factors relating to the patient, pharmacist and the influence of the pharmaceutical industry; as well as the patients lack of knowledge and lack of information. Members of the group agreed that the emergence of resistance should be monitored at the level of healthcare institutions. Conclusion. Identification of factors that influence inappropriate prescribing of antibiotics allows implementation of specific interventions with aim of improving antibiotic use and preventing antibiotic resistance, which is of special importance for developing countries where this problem affects their medical, economic and legal systems.